Der Dual als Mittel literarischer Gestaltung in Michael Psellos’ Chronographia - Reinsch, Diether Roderich (Byzantinische Zeitschrift, 2013)
In the study of Byzantine Greek, duals normally, if ever, are only noted in the Indices Graecitatis of modern editions, whereas they are not taken into consideration for the interpretation of texts. In the case of Michael Psellos’s Chronographia, however, it is worthwhile having a closer look on the remarkably numerous duals that appear in this text. In fact, duals in the Chronographia turn out to function in two special ways. They may treat feigned dualities expressed by them in an ironic manner or enhance a context emotively.The present article gives examples for both these functions.